Evaluation of the Professional Learning Community Program for Teachers in Indonesia - Bernard Napitupulu; Budi Wibawanta (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this study is to evaluate the Professional Learning Community program (PLC) ABC school teachers in Indonesia. The research method used is program evaluation with a Context, Input, Process, and Product (CIPP) model with a qualitative approach. The subjects of this research are the academic head, PIC, and teachers. The locations of the subjects of this study were from various school areas in Indonesia, namely Lubuk Linggau, Cikarang, Makassar, and Manado. The instruments used were interview sheets, document study sheets, questionnaire questions, and audio-visual material usage sheets. The data analysis technique used is descriptive statistics and coding. The results of this study indicate that the implementation of the ABC School PLC is still running well and has succeeded in fostering cooperation in accordance with the PLC document. On the other hand, PLC has not succeeded in increasing teacher professionalism and collaboration. The discovery of the difference between cooperation and collaboration is a new discovery in this research. Considering the results of the evaluation using the CIPP model, the PLC program needs to be continued by implementing several improvements that need to be made.